SYNTHESIS OF SILVER NANOPARTICLES USING BIOREDUCTOR OF KETAPANG LEAF EXTRACT (Terminalia catappa) AND ITS POTENTIAL AS SUNSCREEN - Payapo Irfa Apriliyanti; Muhammad Zakir; Nunuk Hariani Soekamto (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2017)
Synthesis of silver nanoparticles is done by the chemical reduction method using the extract of leaves of catappa (Terminalia catappa) which acts as a reducing agent with the use of AgNO3 as the precursors. The results, based on changes in color, pH, and UV-Vis absorption shows color changes from yellow to yellow-brown with a pH of 4 indicating the formation of silver nanoparticles with a wavelength range from 412,50- 404,00 nm for the storage of the first day until the seventh day with a particle size 92,48 nm based on the results of taking the measurements of PSA. Analysis of functional groups that play a role in the synthesis using FT-IR. Characterization using XRD showed that the synthesized form a cubic crystal with a crystal size of 53,48 nm. Silver nanoparticles are used as a sunscreen with a blend of hydroxy cinnamic acid compounds. Testing activities determined sunscreen with SPF values were analyzed using a UV-Vis spectrophotometer. Results of testing the activity of sunscreen alloy nanoparticles of silver and hydroxy cinnamic acid (AHNP) with a concentration of 16 μg/mL - 20 μg/ml showed the consecutive SPF value 20,97; 24,71; 26,41; 28,07 and 31,92. Sunscreen AHNP activity increases with the concentration AHNP. Based on the research results can be concluded that the combination of ultra AHNP has a protective effect (SPF ≥ 15) against UV-B rays.